2018
DOI: 10.3389/fpls.2018.01266
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Functional Analyses of the CRK Gene Family in Cotton Reveals GbCRK18 Confers Verticillium Wilt Resistance in Gossypium barbadense

Abstract: Cysteine-rich receptor-like kinases (CRKs) are a large subfamily of plant receptor-like kinases that play a critical role in disease resistance in plants. However, knowledge about the CRK gene family in cotton and its function against Verticillium wilt (VW), a destructive disease caused by Verticillium dahliae that significantly reduces cotton yields is lacking. In this study, we identified a total of 30 typical CRKs in a Gossypium barbadense genome (GbCRKs). Eleven of these (>30%) are located on the A06 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 86 publications
4
29
0
Order By: Relevance
“…While the nature of these genes is diverse, none of them so far belongs to the CRK family. Recently, the cotton CRK GbCRK18 was shown to play a role in resistance to Verticillium dahliae as silencing this gene by virus-induced gene silencing mediates plant susceptibility 32 . However, it is not known if this gene would confer resistance once introduced into a susceptible accession.…”
Section: Discussionmentioning
confidence: 99%
“…While the nature of these genes is diverse, none of them so far belongs to the CRK family. Recently, the cotton CRK GbCRK18 was shown to play a role in resistance to Verticillium dahliae as silencing this gene by virus-induced gene silencing mediates plant susceptibility 32 . However, it is not known if this gene would confer resistance once introduced into a susceptible accession.…”
Section: Discussionmentioning
confidence: 99%
“…CRK family members in Glycine max were found to be transcriptionally regulated by the biotic stress signals triggering plant immune response [18]. Further, CRK18 in Gossypium barbadense is reported to confer resistance to verticillium wilt resistance [19].…”
Section: Introductionmentioning
confidence: 99%
“…Several genes in cotton that contribute to defence responses against Verticillium wilt have been characterized (Duan et al ., ; Gao et al ., ; Li et al ., , ; Mo et al ., ; Munis et al ., ; Yang et al ., , ; Zhang et al ., ; ; ; ), and studies on these genes provide an ever greater understanding of the bases for disease resistance in cotton. In most of these studies, however, candidate genes were identified in an arbitrary model such as conserved homologue cloning that lacks a genetic basis.…”
Section: Discussionmentioning
confidence: 99%